PHYTOREMEDIATION POTENTIAL OF Salvinia molesta FOR ORGANIC MATTER COFFEE LIQUID WASTE - Maria Ulfah; Syafina Nurussalma; Ipah Budi Minarti (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Coffee liquid waste contains organic matter which can be at risk of increasing water pollution levels. The results of the preliminary research carried out showed that the level of pollution due to coffee liquid waste exceeded the quality standard, with the results of the BOD test results being 23 ppm and COD 72 ppm, so we need a way to reduce pollution. Phytoremediation is a method of natural waste handling using certain plants in collaboration with microorganisms in the media (soil, coral, water) so that it can change contaminants to be reduced or harmless. This study aims to determine the effectiveness of Salvinia molesta phytoremediation in reducing BOD and COD levels. The research design used a completely randomized design (CRD) with four treatments with three replications. The research data were tested using the Analysis of Variety Prints and the Duncan's Multiple Distance Test continued test. The results showed that the effectiveness of Salvinia molesta in reducing BOD levels was found in P3 obtained by an average of 8.37 ppm (73% decrease) and reducing COD levels by an average of 25.37 ppm (73%). Based on these results, it can be concluded that P3 is effective in reducing BOD and COD levels of coffee liquid waste.